Regional Fibronectin and Collagen Fibril Co-Assembly Directs Cell Proliferation and Microtissue Morphology - Sevilla, Carlos A.; Dalecki, Diane; Hocking, Denise C. (PLOS ONE, 2013)
The extracellular matrix protein, fibronectin stimulates cells to self-assemble into three-dimensional multicellular structures by a mechanism that requires the cell-dependent conversion of soluble fibronectin molecules into insoluble fibrils. Fibronectin also binds to collagen type I and mediates the co-assembly of collagen fibrils into the extracellular matrix. Here, the role of collagen-fibronectin binding in fibronectin-induced cellular self-assembly was investigated using fibronectin-null fibroblasts in an in vitro model of tissue formation. High resolution, two-photon immunofluorescence microscopy was combined with second harmonic generation imaging to examine spatial and temporal relationships among fibronectin and collagen fibrils, actin organization, cell proliferation, and microtissue morphology. Time course studies coupled with simultaneous 4-channel multiphoton imaging identified regional differences in fibronectin fibril conformation, collagen fibril remodeling, actin organization, and cell proliferation during three-dimensional cellular self-assembly. Regional differences in cell proliferation and fibronectin structure were dependent on both soluble fibronectin concentration and fibronectin-collagen interactions. Fibronectin-collagen binding was not necessary for either fibronectin matrix formation or intercellular cohesion. However, inhibiting fibronectin binding to collagen reduced collagen fibril remodeling, decreased fibronectin fibril extension, blocked fibronectin-induced cell proliferation, and altered microtissue morphology. Furthermore, continual fibronectin-collagen binding was necessary to maintain both cell proliferation and microtissue morphology. Collectively, these data suggest that the complex changes in extracellular matrix and cytoskeletal remodeling that mediate tissue assembly are driven, in part, by regional variations in cell-mediated fibronectin-collagen co-assembly.